ISOLAMENTO E QUANTIFICAÇÃO DOS COMPOSTOS MAJORITÁRIOS DA GARCINIA GARDNERIANA - Alves Rodrigues, Dayana; Nunes Colim, Alexsandro; Mendes Pereira, Gustavo Antônio; dos Santos, Marcelo Henrique (Intercursos, 2026)
não há